Concurrent active pulmonary tuberculosis and small cell lung cancer: diagnostic challenges and therapeutic insights from a case report - Sun, Meiling; Ji, Huaijun; Liu, Ailing; Xu, Ning (Frontiers in Oncology, 2025)
The coexistence of active pulmonary tuberculosis (TB) and small cell lung cancer (SCLC) is an exceptionally rare clinical phenomenon, presenting significant diagnostic and therapeutic challenges due to overlapping symptoms, radiological findings, and drug interactions. We report the case of a 68-year-old male with a four-month diagnostic journey, involving persistent cough, exertional chest tightness, and multiple inconclusive bronchoscopic examinations. Active TB was confirmed via sputum smear tests identifying acid-fast bacilli, while SCLC was diagnosed later through a third bronchoscopy, supported by elevated progastrin-releasing peptide (ProGRP, 127.28 pg/mL). The patient received a two-month course of anti-TB therapy before initiating four cycles of etoposide-cisplatin chemotherapy, followed by chest radiotherapy. Anti-TB treatment was intermittently paused during chemotherapy cycles to minimize drug interactions, and the patient completed 11 months of therapy. Follow-up imaging showed partial resolution of the left upper lung lesion, with normalized tumor markers (ProGRP: 66.20 pg/mL). However, at 17 months, disease progression was noted with a metastatic lesion in the right lower lobe. This case underscores the complex interplay between TB-induced chronic inflammation and tumor progression, highlighting the need for early tumor marker testing, advanced imaging modalities such as PET-CT, and tailored therapeutic strategies. Multidisciplinary collaboration is critical for optimizing outcomes in such rare and challenging scenarios. Further research into the mechanistic links between TB and SCLC could improve early diagnosis, guide therapeutic decisions, and inform preventive strategies.